2009
DOI: 10.3144/expresspolymlett.2009.6
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic stretching of grafted maleic acid copolymer chains

Abstract: Abstract. We report on the swelling behaviour of thin maleic acid copolymer films in dependence of pH and ionic strength. The response of the polymer films was studied by quartz crystal microbalance with dissipation monitoring. It was found that solution's pH and ionic strength can be separately used to adjust the swelling of the maleic acid copolymer films. While the pH affects the degree of dissociation of the maleic acid groups, ionic strength triggers the interaction of the resulting charges along the poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…The mass increase can be attributed to the incorporation of water into the swollen film. 34,40 The swelling of the polymer film concomitantly led to a softer film characteristic with a higher viscous contribution as it becomes obvious from the increasing dissipation signal.…”
Section: Qcm-d Analysis Of Copolymer Film Swellingmentioning
confidence: 99%
See 1 more Smart Citation
“…The mass increase can be attributed to the incorporation of water into the swollen film. 34,40 The swelling of the polymer film concomitantly led to a softer film characteristic with a higher viscous contribution as it becomes obvious from the increasing dissipation signal.…”
Section: Qcm-d Analysis Of Copolymer Film Swellingmentioning
confidence: 99%
“…The swelling behaviour of the resulting copolymer films was characterised in detail using quartz crystal microbalance with dissipation monitoring (QCM-D). This analytical technique is highly sensitive for dynamic changes of mass and layer thickness 34 and allows for the in situ variation of temperature and the continuous exchange of aqueous solution. 35 Using this method we studied the functionality of the immobilised SRP films and we could clarify the phase transition behaviour of the grafted copolymers layers.…”
Section: Introductionmentioning
confidence: 99%
“…9 It has been shown that variation of the electrolyte concentration in the bulk medium can lead to non-negligible changes in the electrohydrodynamic properties of soft matters, for example, the electrostatic potential and the binding site distribution through swelling or shrinking process. [10][11][12] In light of this experimental evidence, the theory developed by Duval et al for soft colloids has been recently extended to investigate the influence of ionic strength on the lability criterion and complex stability constant. 13 Nevertheless, to our knowledge, there are no experimental reports that deal with the influence of ionic strength on the electrostatics and dynamic features of metal complex formation with soft colloids.…”
Section: Introductionmentioning
confidence: 99%